2023
DOI: 10.3390/nu15133032
|View full text |Cite
|
Sign up to set email alerts
|

Carvacrol Improves Vascular Function in Hypertensive Animals by Modulating Endothelial Progenitor Cells

Abstract: Carvacrol, a phenolic monoterpene, has diverse biological activities, highlighting its antioxidant and antihypertensive capacity. However, there is little evidence demonstrating its influence on vascular regeneration. Therefore, we evaluated the modulation of carvacrol on endothelial repair induced by endothelial progenitor cells (EPC) in hypertension. Twelve-week-old spontaneously hypertensive rats (SHR) were treated with a vehicle, carvacrol (50 or 100 mg/kg/day), or resveratrol (10 mg/kg/day) orally for fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…EPC migration, increasing CFU production, expression of eNOS, surface antigens (CD31 and CD34), and reduction in ROS and senescence (aging) were observed as a result of getting carvacrol. In other words, carvacrol, modified endothelial dysfunction, and EPC function (Gonçalves et al., 2023 ). The action mechanism of calcium channels and transient receptor potential (TRP) channels in normotensive rats by applying intravenous (i.v) administration of carvacrol (1, 5, 10, and 20 mg/kg) was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…EPC migration, increasing CFU production, expression of eNOS, surface antigens (CD31 and CD34), and reduction in ROS and senescence (aging) were observed as a result of getting carvacrol. In other words, carvacrol, modified endothelial dysfunction, and EPC function (Gonçalves et al., 2023 ). The action mechanism of calcium channels and transient receptor potential (TRP) channels in normotensive rats by applying intravenous (i.v) administration of carvacrol (1, 5, 10, and 20 mg/kg) was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Marketou et al reported that EPCs are involved in arterial stiffness and remodeling in hypertensive patients [9], suggesting EPCs might be used as a therapeutic target. Indeed, Medeiros and colleagues found that a phenolic monoterpene called carvacrol can improve vascular function in hypertensive rats by improving the EPC migration, increasing colony-forming units, and reducing reactive oxygen species production [10]. Numerous studies have also demonstrated that physical exercise can stimulate the mobilization of EPCs and promote EPC differentiation, thereby enhancing the angiogenesis capability of EPCs and contributing to vascular repair [11].…”
Section: Introductionmentioning
confidence: 99%